Analysis of Differences of Mathematics Tadris Curriculum, Mathematics Education in PTKIN and PTUN Based on IndoMS Minimum Recommendations - Mutijah, Mutijah (Study Program of Mathematics Education of Unimed Postgraduate Program, 2024)
Knowledge of amount of credits in certain curriculum groups is considered important to know compliance with a mutually agreed upon curriculum from IndoMS. Two aims of this research results article to investigate the differences in course materials of curriculum of Mathematics Tadris at PTKIN, Mathematics Education at PTKIN and PTUN and illustrate how they differences statistically. One Way Variance Analysis to analyze whether there are differences at overall and each course materials of mathematics in the recommended curriculum by IndoMS. Sample were all PTKIN and PTUN in Java, Jakarta and Special Region of Yogyakarta registered on the internet a number of 18 was taken from those who uploaded their curriculum. Descriptive statistics to describe amount of minimum, maximum, and average of adopted credits, and whether or not there are those who adopt the same. The result showed that in general, there is no difference in the Mathematics Education Curriculum at PTUN and PTKIN as well as the Mathematics Tadris at PTKIN in adopting credits for course materials. While for each there are no differences in Discrete Mathematics, Statistics and Probability Theory, Complex Functions, Introduction to Real Analysis, Introduction to Numerical Analysis, Algorithms and Programming, Differential Equations, Linear Programs, and Mathematical Modeling, but there are differences in Differential and Integral Calculus, Algebra, and Geometry. The Mathematics Education Curriculum at PTUN and PTKIN as well as Mathematics Tadris mostly adopt minimum credits less than those recommended by IndoMS. Maximum credits of Mathematics Education at PTUN and Mathematics Tadris curriculum adopts more than and Mathematics Education curriculum of PTKIN adopts the same. Above 50% of Mathematics Education curriculum at PTUN adopts more than, while Mathematics Education and Tadris at PTKIN adopt less than. In the Mathematics Education Curriculum at PTUN and PTKIN as well as Tadris,a few of them have adopted the same